Towards Digital Health Transformation: The Urgency of Electronic Student Health Reports (Case Study in SD Negeri Cipedak 03, South Jakarta and Puskesmas Jagakarsa) - Retnowati, Retnowati; Siregar, Kemal N; Nurizin, Dion Zein; Ilyas, Arief Azhari (Jurnal Biostatistik, Kependudukan, dan Informatika Kesehatan, 2023)
The community health center (Puskesmas) routinely collects student health examination data in health report books, causing storage, monitoring, and analysis difficulties. This has led to suboptimal health interventions involving parents, schools, and Puskesmas. This research analyzes user needs in developing an electronic-based student health report. This qualitative descriptive study employs the Framework for the Application of System Thinking (FAST) approach. The research was conducted at the Puskesmas Jagakarsa and SD Negeri Cipedak 03, South Jakarta. The study findings indicate utilizing student health report books is not optimal. Based on the needs analysis, there is a necessity to develop an electronic-based student health record. Automated calculation processes and reporting need to be provided by the system with data-sharing mechanisms among users. An interactive and informative dashboard displaying BMI graphs, nutritional status, stunting, anemia, and other physical examination results (dental, eye, ear, hypertension, and others) is essential. A comprehensive and continuous student health history is needed, showing parental health history, student health history, and student immunization history. Digital health transformation in the form of an electronic-based Student Health Report is highly required. This system is expected to enhance the role of parents, schools, and Puskesmas in effectively monitoring student health.